A Study of Temperature-dependent Fluid Properties on MHD Free Stream Flow and Heat Transfer over a Non-Linearly Stretching Sheet. (2015) - Poply, Vikas; Singh, Phool; Yadav, A.K.
Abstract: An analysis has been done for non-linearly stretching sheet with temperature-dependent fluid properties with free stream mag- netohydrodynamic (MHD) flow. The transverse magnetic field and the stretching velocity are assumed to vary as a power of the distance. The thermal conductivity shows linear variation whereas the fluid viscosity varies inversely with temperature. We have incorporated similarity transformations in our study to mould partial differential equations into non-linear equations. These equations are solved using Runge-Kutta Fehlberg method with the shooting techniques. In the present study, we discuss effects of various fluid parameters on the profiles of velocity and temperature in the presence of free stream. The effect with variations of these parameters has been investigated. We found that the free stream velocity reduces the boundary layer thickness.